1992
DOI: 10.1002/mcs.1220040506
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of migration times and propagation of error in micellar electrokinetic chromatography

Abstract: Abstract. The contributions of several factors (electroosmosis, capacity factor, and elution range) to migration time reproducibility have been evaluated using the theory of error propagation. Experimentally obtained values confirm that a single factor, electroosmosis, can explain most of the observed variability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…Since solubilization, the interaction of solute with micelles, operates as a distribution process, the primary driving force is the hydrophobic interaction between the solutes and micelles [2,3]. Hence, retention data involve the information related to the interaction between the solute and the micelle, and in turn to the hydrophobicity of the analyte [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Since solubilization, the interaction of solute with micelles, operates as a distribution process, the primary driving force is the hydrophobic interaction between the solutes and micelles [2,3]. Hence, retention data involve the information related to the interaction between the solute and the micelle, and in turn to the hydrophobicity of the analyte [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…In line with data in Table 1 we observed that the repeatability of migration times in the three systems under consideration is broadly identical. This observation is further reinforced by the broadly identical repeatability of peak areas as in CE the observed peak areas are affected by the velocity of migration of the separated zones [ 22 , 23 ].…”
Section: Resultsmentioning
confidence: 87%
“…These criteria can be satisfied by the use of MECC. Reproducibility of separations in MECC and CZE has been addressed by various researchers [12][13][14][15][16][17][18][19][20]. Some previous discussions of reproducibility have centered on the analysis of standards [14-151, Reagents.…”
Section: Introductionmentioning
confidence: 99%